Commentary on “Discussion on ‘function-weighted frequency response function sensitivity method for analytical model updating’ by A. Esfandiari and M. Sanayei" - Lin Rongming (2021)
We would like to thank A. Esfandiari and M. Sanayei [1] for their interests and comments on our work “function-weighted frequency response function sensitivity method for analytical model updating” previously published in the Journal of Sound and Vibration [2]. The primary objective of our work was to explore the possibilities of further enhancing the numerical solution process associated with finite element model updating using FRF data by exploiting the known mathematical characteristics of the receptance sensitivities at each design point during the iterations. There is some obvious misunderstanding about the basic concept that we sought to convey in our paper [2], either because of the way we presented the material which somehow lacks clarity, or because of the mathematical complexity associated with the work, leading to difficulties in understanding well how the proposed method actually works. This commentary serves to address these concerns by (i) introducing simple generic mathematical examples to illustrate how the proposed method works, without getting involved with the mathematical complexities of model updating practice, (ii) further discussing the mathematical concept and deriving analytically the key receptance sensitivities and, (iii) providing additional numerical results to support and demonstrate the key characteristics of receptance sensitivities.